Integrasi Nilai-Nilai Islam dalam Budaya Kerja Milenial dan Gen Z - Indi Rahmah (Moral : Jurnal kajian Pendidikan Islam, 2025)
The transformation of the workplace driven by digitalization and generational value shifts has introduced new challenges in maintaining ethical and organizational culture, particularly among Millennials and Gen Z. This study aims to examine the extent to which Islamic values—especially through Islamic Work Ethics (IWE) and spiritual intelligence—are integrated in shaping the work culture of young professionals. Using a quantitative approach, data were collected via surveys from 150 respondents working in the startup, Islamic banking, and educational sectors in the Greater Jakarta area. Data were analyzed using Pearson correlation and path analysis via SmartPLS. The results show that both IWE and spiritual intelligence have a positive and significant effect on work culture, with a combined contribution of 56%. These findings indicate that integrating Islamic values can foster an ethical, productive, and spiritually aligned work culture among younger generations. The study has theoretical implications for developing a contextual Islamic work culture framework, and practical implications for organizations seeking to design policies grounded in spiritual and Islamic ethical principles